The Role of Defense Technology in an Effort to Achieve Indonesia as a World Maritime Axis - Widia Aprilia (CV. Rayyan Dwi Bharata, 2023)
Indonesia has a challenge to ensure that the security and defense of the maritime area are well managed, this is related to the reality of Indonesia as the largest archipelagic country that has strategic waterways. One way to achieve this goal is to make Indonesia a World Maritime Axis (PMD). With this reality, Indonesia needs to pay attention to several aspects, especially in the economic, technology, and defense and security sectors. In this study the method used for writing is descriptive qualitative literature study.